Analisis Semiotika Sosial dalam Teks Kampanye Pemasaran Bangga Buatan Indonesia - Rinaldo Hermawan (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
This study analyzes the meaning construction of the Bangga Buatan Indonesia (BBI) campaign using Halliday's social semiotics approach to examine the consistency of the campaign's message and its persuasive potential in shaping attitudes and intentions to consume local products. Data for the study was collected from three primary sources: the BBI logo, the official Instagram captions, and eight promotional videos produced by various stakeholders, including ministries, e-commerce platforms, business owners, and the media. The analysis reveals a discrepancy in the discourse between the organic campaign message and its development by various text producers. The official narrative emphasizes solidarity and unity during the pandemic but fails to explicitly link pride with local products, while other text producers interpret the notion of "pride" in various ways without a consistent meaning foundation. This inconsistency weakens the continuity and coherence of the campaign's narrative. The findings of the study underscore that narratives focusing on patriotism and moral obligation are more effective in generating consumption interest than symbolic superiority conveyed through the use of the term "pride," which lacks a consistent rationalization.